Characterization of retinoic acid–induced neurobehavioral effects in developing zebrafish. (2nd January 2014) - Wang, Yujiang; Chen, Jiangfei; Du, Changchun; Li, Chunqi; Huang, Changjiang; Dong, Qiaoxiang
Abstract Retinoic signaling plays an important role in cell proliferation and differentiation. Disruption of retinoic signaling via excessive or deficient retinoic acid can cause teratogenic effects on developing embryos. Similar to retinoic acid, many xenobiotic environmental pollutants have been found to disrupt retinoic signaling through binding and eliciting agonistic activity on retinoic acid receptors. Currently, studies of retinoic acid or retinoic acid–like compounds in aquatic organisms have mainly focused on teratogenicity and few studies have explored their neurobehavioral toxicity. In the present study, the authors used retinoic acid as an example to explore the neurobehavioral toxicity associated with developmental exposure of retinoic acid–like compounds in zebrafish. The findings confirmed retinoic acid's teratogenic effects such as bent spine, malformed tail, and pericardial edema in developing zebrafish with a median effective concentration of 2.47 nM. Retinoic acid–induced cell apoptosis at 24 h postfertilization was consistently found in the eye and tail regions of embryos. Spontaneous movement as characterized by tail bend frequency was significantly increased in zebrafish embryos following exposure to 2 nM and 8 nM retinoic acid. Relatively low‐dose retinoic acid exposure of 2 nM led to fast locomotion behavior in the dark period and hyperactivity during light–dark photoperiod stimulation. The 2‐nM retinoic acid exposure also led to alterations of neurobehavior‐ and optic nerve–related genes, with the transforming growth factor‐β signal transduction inhibitor noggin (nog) and the spinal cord marker homeobox c3a (hox) being underexpressed and the retinal G protein–coupled receptor a (rgr), the photoreceptor cell marker rhodopsin (rho), and the short wave–sensitive cone pigment opsin 1 (opn1sw1) being overexpressed. Increased expression of opn1sw1 and rho was confirmed by whole‐mount in situ hybridization. Whether the misexpression of these genes leads to the neurobehavioral changes merits further study. The findings demonstrated that low‐dose retinoic acid exposure perturbed the visual system and optic nerve development and caused hyperactivity in developing zebrafish. Environ Toxicol Chem 2014;33:431–437. © 2013 SETAC